Diagnostic Symptoms of Corona Audible Noise in Continuous Monitoring Systems - WSZOŁEK, Tadeusz (Archives of Acoustics, 2011)
Random nature of corona processes in UHV power lines and the accompanyingnoise is the reason that in practice the best determination of acoustic parameters,necessary for the noise evaluation, is obtained from the continuous monitoring procedure.However because of considerable fluctuations (both the useful signal partand the interfering components), careful selection of monitored parameters is necessaryto enable a possibility of automatic determination of the parameters that arerequired for long-term evaluation of corona noise.In the present work a practical realization is shown for estimation of coronanoise parameters, based on the data obtained from continuous monitoring stations,making use of the statistical spectra measurement and characteristic features ofcorona process acoustic signal.Selected results are presented from continuous monitoring of corona noise generatedat a 400 kV power line, with special attention focused on definitions of themeasured quantities, which enable automatic estimation of the basic factors requiredfor noise evaluation. Accompanying monitoring of environmental conditions,including humidity, precipitation intensity and fog density, that are well correlatedwith the corona process intensity, which might definitely increase the filtration efficiencyof environmental disturbances and on the other hand, it enables verificationof calculation methods applied to corona noise.The paper also contains a description of practical approach to selection signalparameters of corona noise in continuous monitoring stations.